(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
This study examined the generational digital divide in Nigerian workplaces, focusing on how differences in digital literacy impact communication, collaboration, and overall productivity. Grounded in Generational Cohort Theory and Human Capital Theory, the research explored the unique challenges faced by different generational groups and how their varying experiences with technology shape workplace dynamics. A descriptive survey design was employed, gathering data from 283 respondents across different industries. Findings revealed while most employees are comfortable with digital tools, generational differences create significant communication barriers in the workplace. Results also indicated that older employees face challenges such as fear of making mistakes, insufficient training, and workplace cultures that favour younger, tech-savvy workers. Respondents sampled for this study emphasized that strategies such as regular digital skills training, mentorship programs pairing younger and older employees, and fostering an inclusive, learning-oriented culture are essential for bridging the generational gap in the digital age. The study concluded that sustained investment in cross-generational training, empathetic leadership, and accessible technology is vital to enhancing workplace cohesion and productivity in Nigeria’s evolving digital landscape.